CIRCUMSTANTIAL EVIDENCE DAN NARASI YUDISIAL DALAM PERKARA JESSICA WONGSO DAN MADELEINE SMITH - Zul Khaidir Kadir (SINERGI : Jurnal Riset Ilmiah, 2026)
Murder cases based on circumstantial evidence raise a central problem in criminal adjudication because courts must transform fragmented facts into a legally persuasive narrative without allowing suspicion to replace proof. This article aims to examine how judicial narrative is constructed through evidentiary inference in two poisoning cases, namely Jessica Wongso in Indonesia and Madeleine Smith in Scotland. The study employs a document-based doctrinal-comparative method by analyzing the cause of death, poison medium, access or opportunity, attribution of conduct, treatment of alternative possibilities, and the final form of verdict. The findings show that courts do not merely assess evidentiary fragments in isolation, but arrange them into a narrative that establishes sequence, causality, and a basis for accepting or rejecting conviction. In the Jessica Wongso case, the connection between the victim’s death, cyanide, coffee as the medium, control over the drink, and other surrounding facts was regarded as sufficient to sustain a guilty verdict. In the Madeleine Smith case, strong suspicion arose from personal relations, arsenic purchases, and circumstances incriminating the accused, yet the connection between poison, opportunity, and act was not considered sufficient to justify conviction. The implication of this comparison is that circumstantial evidence should not be evaluated only through narrative coherence, but also through the strength of inferential links and the disciplined assessment of alternative possibilities.